Eutectics: When Eutectics Meet Plasmonics: Nanoplasmonic, Volumetric, Self‐Organized, Silver‐Based Eutectic (Advanced Optical Materials 3/2015). Issue 3 (March 2015) - Sadecka, Katarzyna; Gajc, Marcin; Orlinski, Krzysztof; Surma, Hancza B.; Klos, Andrzej; Jozwik‐Biala, Iwona; Sobczak, Kamil; Dluzewski, Piotr; Toudert, Johann; Pawlak, Dorota A.
<x xml:space="preserve">Abstract</x> Nanoplasmonic, volumetric, self‐organized, silver‐based eutectics exhibit localized surface plasmon resonances (LSPRs) at visible wavelengths after annealing. K. Sadecka, D. A. Pawlak, and co‐workers demonstrate on page 381 how, in transmitted light, the sample shows a blue coloration: the complementary wavelength to the yellow light absorbed due to the LSPR at about 590 nm. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>